BIOLOGICAL PROPERTIES OF LACTOBACILLI ─ OYSTER MUSHROOM RESIDENTIAL MICROBIOTA REPRESENTATIVES - О. В. Басюл; Г. В. Ямборко; В. О. Іваниця (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2014)
The aim of the investigation was lactobacilli strains isolation from Pleurotus ostreatus oyster mushroom fresh and fermented fruiting bodies and study of their biological and biotechnological properties. Methods. Investigation objects were 50 lactobacilli strains isolated from Pleurotus ostreatus oyster mushroom fresh and fermented fruiting bodies. Lactobacilli genus and species belonging were determined by morphological, cultural, physiological, biochemical properties and confirmed by PCR method with primers to 16S РНК and recA. Lactobacilli strains acid producing degree was investigated by incubation in skimmed milk for 1, 15 and 24 hours, limit acidity – by week incubation, lactic acid percentage – by titration method. Lactobacilli antagonism was determined by agar blocks method. Results. Lactic acid bacteria are considered to be a part of Pleurotus ostreatus fruiting bodies microbiota. 8 lactobacilli strains, isolated from fresh and fermented mushrooms, were identified by morphological, cultural and physiology-biochemical properties as the Lactobacillus plantarum species, that was confirmed by PCR method. Investigated lactobacilli strains produce from 0.5 ± 0.1 to 1.4 ± 0.2% of lactic acid for 15 hours, and acidity is 144−300 0Т. Conclusion. Strain L. plantarum ONU315, isolated from Pleurotus ostreatus oyster mushroom fresh and fermented fruiting bodies, is active acid producer with high and medium level antagonistic activity to opportunistic bacteria, bacteria − oyster mushroom representatives, do not show antagonism to other species lactic acid bacteria.